‘Tasting imagination’: what role chemosensory mental imagery in multisensory flavour perception? - Spence, C (Brill, 2022)
A number of perplexing phenomena in the area of olfactory/flavour perception may fruitfully be explained by the suggestion that chemosensory mental imagery can be triggered automatically by perceptual inputs. In particular, the disconnect between the seemingly limited ability of participants in chemosensory psychophysics studies to distinguish more than two or three odorants in mixtures and the rich and detailed flavour descriptions that are sometimes reported by wine experts; the absence of awareness of chemosensory loss in many elderly individuals; and the insensitivity of the odour-induced taste enhancement (OITE) effect to the mode of presentation of olfactory stimuli (i.e., orthonasal or retronasal). The suggestion made here is that the theory of predictive coding, developed first in the visual modality, be extended to chemosensation. This may provide a fruitful way of thinking about the interaction between mental imagery and perception in the experience of aromas and flavours. Accepting such a suggestion also raises some important questions concerning the ecological validity/meaning of much of the chemosensory psychophysics literature that has been published to date.